Influence of support surfaces on the distribution of body interface pressure in surgical positioning - Karoline Faria de Oliveira; Patrícia da Silva Pires; Ana Lúcia De-Mattia; Elizabeth Barichello; Cristina Maria Galvão; Cleudmar Amaral de Araújo; Maria Helena Barbosa (Universidade de São Paulo, 2018)
Abstract Objective: to evaluate the interface pressure (IP) of support surfaces (SSs) on bony prominences. Method: a quasi-experimental study with repeated measures on each SS. Twenty healthy adult volunteers participated in the study. The participants were placed in the supine position on a standard operating table for evaluation of IP on the bony prominences of the occipital, subscapular, sacral, and calcaneal regions using sensors. Seven evaluations were performed for each bony prominence: one on a standard operating table, and the others on tables containing SSs made of viscoelastic polymer, soft foam, or sealed foam. Descriptive statistics and analysis of variance were used to analyze the data. Results: the mean IP was higher on the viscoelastic polymer-based SS compared to the other SSs (p<0.001). The mean IP was relatively lower on the density-33 sealed foam and density-18 soft foam. In addition, this variable was comparatively higher in the sacral region (42.90 mmHg) and the calcaneal region (15.35 mmHg). Conclusion: IP was relatively lower on foam-based SSs, especially on density-18 soft foam and density-33 sealed foam. Nonetheless, IP was not reduced on the viscoelastic polymer SS compared to the control SS.